Genetic diversity of Bartonella rpoB haplotypes in domestic cats from Chile - Sepúlveda-García, Paulina; Jara, Ronald; Mella, Armin; Monti, Gustavo; Canales, Nivia; Furquim, Maria Eduarda Chiaradia [UNESP]; André, Marcos Rogério [UNESP]; Müller, Ananda (Elsevier, 2024)
The study aimed to determine the inter and intra-host Bartonella spp. genetic diversity in cats from Chile. ‘Seventy-nine cats’ blood DNA samples qPCR Bartonella spp. positive were subjected to T-A cloning of Bartonella spp. rpoB partial gene (825 bp), and sequencing by Sanger method. The sequences were submitted to phylogenetic and polymorphism analysis. Thirty-six (45.6%) samples were successfully cloned, generating 118 clones of which 109 showed 99.6%–100% identity with Bartonella henselae whereas 9 showed 99.8–100% identity with Bartonella koehlerae. Haplotype analysis yielded 29 different rpoB-B. henselae haplotypes, one (hap#2) overrepresented in 31 out of 33 cats, and 4 rpoB-B. koehlerae haplotypes, with hap#2 represented in all 3 B. koehlerae infected cats. More than one rpoB -B. henselae and B. koehlerae haplotypes were identified in individual cats, reporting by first time coinfection by different B. henselae/B. koehlerae rpoB variants in cats from Chile.
Keywords: Bartonella spp; Cloning; Coinfection; Genetic diversity